Malignant eccrine poroma: report of three cases. Issue 10 (October 1986) - Ryan, J F; Darley, C R; Pollock, D J
Abstract : The characteristic clinical and histological features of three cases of malignant eccrine poroma are discussed, in addition to the metastatic disease that had occurred in two cases. These cases were compared with previously reported cases of malignant eccrine poroma that had metastasised, and it is suggested that a strict classification of malignant eccrine sweat gland tumours should be made.